Perfil protéico do plasma seminal de suínos e sua associação com a qualidade do sêmen congelado - Corcini, Carine Dahl (2008)
Artificial insemination (AI) in swine with frozen semen presents lower reproductive performance than AI with cooled semen. Such inefficiency can be attributed to many factors, especially to the semen extenders and individual boar effects, since boars may have different protein content in their seminal plasma. The objective of this study was to evaluate the protein content of distinct portions of the ejaculate of boars, prior to freezing, and the association between the presence of the proteins in the seminal plasma and parameters of semen quality post-thawing, to identify biochemical markers potentially associated with semen freezability in different boars and portions of the ejaculate. The sperm-rich portion of the ejaculate was fractioned in two samples, which were frozen in an extender containing 5% dimethylacetamide as a penetrating cryoprotectant. The protein content of the seminal plasma was evaluated through unidimensional electrophoresis and associated with sperm motility and membrane integrity, pre-freezing and post-thawing, and to sperm morphology and acrossome integrity post-thawing. Inter-boar analyses were conducted, adjusting for individual effects, as well as intra-boar analyses, which were stratified by boar. The first portion of the ejaculate, consisting of the first collected 10 mL, presented better post-thawing semen quality than the second portion. Nine proteins present in the seminal plasma presented significant association with parameters of semen quality (P < 0.05), in both inter and intra-boar analyses. Among them, two proteins, having molecular weight of 28 and 100 kDa were associated, respectively, with post-thawing sperm motility and both pre-freezing and post-thawing sperm membrane integrity. Thus, such proteins are potential biochemical markers for boar semen quality.